Human Rights of Mentally Ill Clients - Hitesh Sheth, Dr (International Journal of Psychosocial Rehabilitation, 2016)
Human rights are important for all strata, classes and races of the society. But it assumes special significance for mentally ill clients, who because of their vulnerability due to illness, often fail to prevent violation of their rights. Often the violation of rights occurs right from the admission in mental hospital, until discharge from the hospital. Frequently, the same violations of the rights of the mentally ills also occur in prisons, shelter homes and streets. Often the very efforts to protect the rights of mentally ill clients lead to violation of the rights. The group, which is marginalized, discriminated and stigmatized by the society, can only be helped by the society. The society can help the mentally ill clients by enacting laws favorable for them, by providing proper facilities for community based treatment, protecting their rights at mental hospitals and by rehabilitating them in society after discharge from the hospital